VIAJANDO COM A MATEMÁTICA – UM RECURSO EDUCACIONAL DIGITAL PARA O ENSINO FUNDAMENTAL - Portella, Zeni M. S.; Moraes, Sidonia R. D. M. d.; Eickhoff, Fernando; Soares, Carine G. T.; Pereira, Tânia M.; Brizzi, Maristela L. S. (Salão do Conhecimento, 2013)
Resumo